Pencegahan Stunting dengan Edukasi dan Terapi Tuina Massage pada Balita di RW 004 RT 003 Kelurahan Bambu - Heryandi, Rifki; Susanti, Fajar; Samsuni, Samsuni (Jurnal Nusantara Mengabdi, 2024)
Purpose: This service aims to improve the knowledge, attitudes, and skills of mothers of toddlers to prevent stunting using tuina massage. Providing tuina massage, it is hoped that it can increase appetite in toddlers and increase body weight in toddlers who experience difficulties when the toddler's appetite decreases. Research methodology: The method in this research uses assessment of toddlers who experience difficulties in fulfilling nutrition by providing pre-tests and post-tests in providing understanding to mothers of toddlers, health education to mothers and toddlers about stunting, demonstrating tuina massage to mothers of toddlers, question and answer discussions and evaluation of outreach activities health. Results: The results of community service showed significant figures after being implemented in the form of health education for mothers of toddlers with an increase in knowledge about standing by 60%, attitudes by 52%, and skills by 55%. Conclusions: Based on community service activities with the title Stunting Prevention Using Tuina Massage Education and Therapy for Toddlers in Rw 004 Rt 003 Bambu Apus Village, East Jakarta, it can be concluded that community service activities run smoothly and receive support from the village government, stunting prevention education using tuina massage increases knowledge, attitudes, and skills of mothers of toddlers. Community service activities by the tri dharma of higher education are useful for opening insight into preventing stunting using tuina massage to increase children's appetite. Limitations: Tuina massage should be done for 6 consecutive days, but due to time constraints it will only be done once. Contribution: This community service is expected to be a reference in scientific development for babies experiencing stunting with prevention using tuina massage. Apart from that, hopefully, it can increase further knowledge about the mechanism of tuina massage.